DYNAMIC RELATIONSHIP BETWEEN ENERGY SUBSIDY AND FISCAL DEFICIT IN INDONESIA - Iba, Zainuddin; Bariah, Chairul; Musrizal, Musrizal; Hendiyan, Dina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Problem the fiscal deficit still has a bad influence on the increase in government debt every year. So far, the government has tended to withdraw new debt to cover the fiscal deficit.In conditions of negative primary balance, debt withdrawals tend to increase deficits and fiscal failures in the long run. This condition is also exacerbated by the Covid-19 that hit Indonesia. The deficit has exceeded 3 percent of GDP. even though the state finance law is a maximum of 3 percent of GDP. This condition has had a bad influence on people's purchasing power. caused by a decrease in purchasing power of goods and services. In dealing with this condition, the government needs to increase people's purchasing power through price regulation. Energy subsidiesclosely related to fiscal policy and a number of macroeconomic variables such as: inflation, exchange rates and BIR.This study aims to determine the relationship between energy subsidy control and fiscal deficit, in order to obtain an optimal fiscal deficit. Through the control of energy subsidies, the optimal value of the fiscal deficit can be obtained. Subsidy controls also affect the amount of government debt, so that optimal debt is obtained.